Knowledge, Attitude and Practice towards Dietary Salt Intake among Nurses Working in a Cardiac Hospital in Bangladesh Sciences - Mondal, Rajib; Sarker, Rajib Chandra; Sayrin, Rumana; Afrin, Rubya; Zaman, Khurshid; Acharya, Narayan Prasad; Sultana, Sharmin; Banik, Palash Chandra; Faruque, Mithila; Choudhury, Sohel Reza; Zaman, M Mostafa (Cardiovascular Journal, 2019)
Background: Noticeable proportion of Bangladeshi population including health professionals is habituated with excessive salt intake although having a good knowledge and attitude. There is no related data regarding salt intake practice among nurses in Bangladesh. The aim of this study was to assess the knowledge, attitude and practice towards dietary salt intake among the nurses working in a selected cardiac hospital. Methods: A cross-sectional study was conducted among 211 nurses working in National Heart Foundation Hospital and Research Institute (NHFHRI), Dhaka. The NHFHRI was selected purposively and all of the nurses were targeted to recruit. Modified WHO Salt Module of STEPS Questionnaire was used for data collection. Results: All of them believed that too much salt in diet could cause serious health problems, and majority (76.8%) had average knowledge regarding the health effects of excess salt intake. More than eighty percent (83.4%) believed that lowering the salt in diet is very important and about two-third (62.6%) used to consume salt just the right amount. Almost half (49.3%) of the nurses were used to add extra salt during their meal and three-quarter (76.8%) were used to take high salt content processed food. The median of extra salt intake among the always users (n=52) was found 2.5 g per day. Conclusion: In spite of having good knowledge and positive attitude towards dietary salt intake, the added salt intake behavior was noteworthy among the nurses working in NHFHRI. Cardiovasc. j. 2019; 12(1): 53-58